Neural Stem Cells of the Subventricular Zone as the Origin of Human Glioblastoma Stem Cells. Therapeutic Implications - Matarredona, Esperanza R.; Pastor, Angel M. (Frontiers in Oncology, 2019)
Human glioblastoma is the most aggressive type of primary malignant brain tumors. Standard treatment includes surgical resection followed by radiation and chemotherapy but it only provides short-term benefits and the prognosis of these brain tumors is still very poor. Glioblastomas contain a population of glioma stem cells (GSCs), with self-renewal ability, which are partly responsible for the tumor resistance to therapy and for the tumor recurrence after treatments. The human adult subventricular zone contains astrocyte-like neural stem cells (NSCs) that are probably reminiscent of the radial glia present in embryonic brain development. There are numerous molecules involved in the biology of subventricular zone NSCs that are also instrumental in glioblastoma development. These include cytoskeletal proteins, telomerase, tumor suppressor proteins, transcription factors and growth factors. Interestingly, genes encoding these molecules are frequently mutated in glioblastoma cells. Indeed, it has been recently shown that NSCs in the subventricular zone are a potential cell of origin that contains the driver mutations of human glioblastoma. In this review we will describe common features between GSCs and subventricular zone NSCs, and we will discuss the relevance of this important finding in terms of possible future therapeutic strategies.